Sarcopenia, obesity and sarcopenic obesity: effects on liver function and volume in patients scheduled for major liver resection. Issue 2 (28th April 2015) - Lodewick, Toine M.; Roeth, Anjali A.J.; Olde Damink, Steven W.M.; Alizai, Patrick H.; van Dam, Ronald M.; Gassler, Nikolaus; Schneider, Mark; Dello, Simon A.W.G.; Schmeding, Maximilian; Dejong, Cornelis H.C.; Neumann, Ulf P.
Abstract: Background: Sarcopenia, obesity and sarcopenic obesity have been linked to impaired outcome after liver surgery. Preoperative liver function of sarcopenic, obese and sarcopenic‐obese patients might be reduced, possibly leading to more post‐operative morbidity. The aim of this study was to explore whether liver function and volume were influenced by body composition in patients undergoing liver resection. Methods: In 2011 and 2012, all consecutive patients undergoing the methacetin breath liver function test were included. Liver volumetry and muscle mass analysis were performed using preoperative CT scans and Osirix ® software. Muscle mass and body‐fat% were calculated. Predefined cut‐off values for sarcopenia and the top two body‐fat% quintiles were used to identify sarcopenia and obesity, respectively. Histologic assessment of the resected liver gave insight in background liver disease. Results: A total number of 80 patients were included. Liver function and volume were comparable in sarcopenic(‐obese) and non‐sarcopenic(‐obese) patients. Obese patients showed significantly reduced liver function [295 (95–508) vs. 358 (96–684) µg/kg/h, P = 0.018] and a trend towards larger liver size [1694 (1116–2685) vs. 1533 (869–2852) mL, P = 0.079] compared with non‐obese patients. Weight ( r = −0.40), body surface area ( r = −0.32), estimated body‐fat% ( r = −0.43) and body mass index ( r = −0.47) showed a weak but significant negative (all P < 0.05) correlation with liver function. Moreover, body‐fat% was identified as an independent factor negatively affecting the liver function. Conclusion: Sarcopenia and sarcopenic obesity did not seem to influence liver size and function negatively. However, obese patients had larger, although less functional, livers, indicating dissociation of liver function and volume in these patients.